Kinematic and static characterization of wrist joints and their optimal design - Asada, H.; Granito, J. (Proceedings. 1985 IEEE International Conference on Robotics and Automation, 1985)
The instantaneous kinematic and static characteristics of wrist joints are analyzed. Velocity ratio and mechanical advantage have been used for characterizing single-input-single-output mechanisms. These concepts are extended to multi-input-multi-output mechanisms in order to analyze robotic devices, specifically, wrist joints. The kinematic and static performance of wrist joints and their singularities are analyzed in terms of the generalized velocity ratio and the generalized mechanical advantage. Methods for avoiding singularities and improving the kinematic and static performances are then presented. The kinematic and static performance is optimized by varying the kinematic structure and the geometry of wrist joints. In particular the geometry of the last link, on which the end effector is mounted, is modified so that the singular points are moved from the middle of the workspace to its boundaries. The kinematic and static performance is further improved by determining the optimal configuration for performing a given task. An optimization method is developed to find the configuration that provides the most uniform velocity ratio and an adequate mechanical advantage in all directions. The kinematic and static performance of two different wrist joints are then evaluated and improved using this design methodology.